The Borgias. The second season [videorecording (DVD)] - Jordan, Neil, 1950- (Showtime Entertainment, 2013)
After exacting vicious punishment on all those who opposed them, the Borgias are at the apex of their power and influence. With the world around them embroiled in war and turmoil, the original crime family will continue to exploit allies, silence critics, and solidify legacies. But this time, the seemingly unbreakable bonds of blood will be tested, as the house notoriously united against the world becomes divided against itself.